Costs of diabetes in Italy - Zaniolo, Orietta (Farmeconomia. Health Economics and Therapeutic Pathways, 2009)
Among chronic diseases, diabetes is one of the most impacting on healthcare expenditures. This impact is expected to continue growing over time, because of increasing prevalence and earlier diagnosis, with subsequent longer duration of the disease. A review of the main Italian cost of illness studies has been conducted, with a focus on papers addressing the cost structure of diabetes care and those exploring the resources determining the expenditure difference between diabetic and non-diabetic patients. According to different sources, in Italy the yearly average direct cost for diabetes management ranges from € 2,340 to 2,990 per patient. Drugs account for 22-34% of this burden, while 52-60% is due to hospitalization. Of the pharmaceutical expenditure, only 10-11% is related to oral hypoglycemic drugs. Complications account for a large share of diabetes costs: vascular complications induce a 70-100% cost increase. Several studies compared health care expenditures for diabetic patients with those for matched control patients without diabetes. These studies point out that diabetic patients have higher health costs due to an increase in the prevalence of use of health care resources and/or an increase in their prescribed amount. As expected, this gap is mainly due to the treatment of diabetes complications, as opposed to routine disease management; furthermore, some evidence showed that cost increases related to diabetes diagnosis are also caused by drugs, hospitalizations and specialist consultations required for managing disorders traditionally considered not related to diabetes. Consistently with international literature data, our review suggests that the improvement of therapy adherence, together with the adoption of strategies specifically prescribed in order to prevent or delay complications, may be able to ameliorate long term clinical and quality of life outcomes, with a marginal increment of health expenditures.